2013
DOI: 10.4081/bam.2013.4.211
|View full text |Cite
|
Sign up to set email alerts
|

Evidence based medicine in physical medicine and rehabilitation (German version)

Abstract: Evidence Based Medicine in Physical Medicine and RehabilitationIn the last twenty years the term "Evidence Based Medicine (EBM)" has been increasingly applied in all areas of medicine and is often used for decision-making in the medical and public health sector. It is also used to verify the significance and/or the effectiveness of different therapies. The original definition of EBM rests on the following three pillars: the physician's individual expertise, the patient's needs and the best external evidence. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The practical applications of no external load training are promising, especially if we consider the adverse effects of inactivity [ 41 , 42 , 43 ]. Previous studies have shown that inactivity might be associated with increased adiposity [ 43 ] and decreases in muscle strength and loss of muscle mass [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The practical applications of no external load training are promising, especially if we consider the adverse effects of inactivity [ 41 , 42 , 43 ]. Previous studies have shown that inactivity might be associated with increased adiposity [ 43 ] and decreases in muscle strength and loss of muscle mass [ 44 ].…”
Section: Discussionmentioning
confidence: 99%